Microarray study of gene expression in uterine leiomyoma - Litovkin, K.V.; Ivanova, O.V.; Bauer, A.; Hoheisel, J.D.; Bubnov, V.V.; Zaporozhan, V.N. (Experimental Oncology, 2008)
Uterine leiomyoma is a most common benign neoplasm in women of reproductive age. It arises from the myometrial compartment of the uterus and may transform in some cases to a malignant phenotype. Aim: To identify the genes involved in pathogenesis of uterine leiomyoma. Methods: We have studied differential gene expression in matched tissue samples of leiomyoma and normal myometrium from the very same people utilizing a cDNA microarray screening method. We also compared our results with previously published microarray data to identify the overlapping gene alterations. Results: Based on this comparison we can divide genes deregulated in our study into two groups. The first group comprises genes that to our knowledge have not been previously reported as deregulated in fibroids: CLDN1, FGF7 (KGF), HNRPM, ISOC1, MAGEC1 (CT7), MAPK12, RFC, TIE1, TNFRSF21 (DR6). The second group consists of genes identified also in previous studies: CCND1 (BCL1), CDKN1A (P21), CRABP2, FN1 and SOX4 (EVI16). In our study FN1 was the most up-regulated gene, occupying the place between the myometrium and fibroids ranging from 2.07 to 3.64, depending of the probe molecule used for detection. Conclusions: Newly identified genes may be regarded as potential diagnostic or prognostic markers of uterine leiomyoma and thus may be very useful as new therapeutic candidates. Лейомиома матки является одним из наиболее распространенных доброкачественных новообразований женской репродуктивной
сферы. В некоторых случаях отмечают злокачественную трансформацию данного новообразования. Цель: идентификация
генов, вовлеченных в патогенез лейомиомы. Методы: проведен анализ дифференциальной экспрессии генов в
образцах лейомиомы и нормального миометрия одних и тех же пациентов методом ДНК-биочип-гибридизации и проведено
сравнение полученных результатов с данными, опубликованными ранее. Результаты: выявлены различия в экспрессии
ряда генов, которые можно разделить на две группы. Впервые выявлена повышенная экспрессия генов CLDN1, FGF7 (KGF),
HNRPM, ISOC1, MAGEC1 (CT7), MAPK12, RFC, TIE1 и TNFRSF21 (DR6) в ткани лейомиомы по сравнению с нормальным
миометрием. Ко второй группе можно отнести гены CCND1 (BCL1), CDKN1A (P21), CRABP2, FN1 и SOX4 (EVI16), уже
упоминавшиеся в связи с патогенезом лейомиомы в ряде предыдущих исследований. Наибольшим изменением уровня экспрессии
(в 2,07–3,64 раз в зависимости от зонда) характеризовался ген фибронектина FN1. Выводы: идентифицированные
гены могут рассматриваться в качестве потенциальных диагностических и прогностических маркеров лейомиомы матки.